2016
DOI: 10.1007/s00384-016-2612-8
|View full text |Cite
|
Sign up to set email alerts
|

Management of postoperative bleeding after laparoscopic left colectomy

Abstract: Postoperative anastomotic bleeding is not so uncommon after left colectomy. This complication should be particularly dreaded in patients who underwent stapled colorectal anastomosis for diverticular disease. With the use of clip or mucosal sclerosis, early endoscopy is a safe and efficient treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…Anastomotic bleeding can present as a severe bleed in approximately 1% of patients [47], and a single significant episode in up to 6% of patients [48, 49]. With the considerations of preserving the anastomosis and achieving safe endoscopy due to active bleeding, management can be challenging.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anastomotic bleeding can present as a severe bleed in approximately 1% of patients [47], and a single significant episode in up to 6% of patients [48, 49]. With the considerations of preserving the anastomosis and achieving safe endoscopy due to active bleeding, management can be challenging.…”
Section: Resultsmentioning
confidence: 99%
“…Besson et al reported their case series of 729 patients undergoing either a laparoscopic or open elective left hemicolectomy over a 9-year time frame [48]. Post-operative bleeding was experienced in 6.4% of patients, of which 97.8% had a stapled anastomosis.…”
Section: Resultsmentioning
confidence: 99%
“…AB has been reported to occur in 6% of patients following left‐sided colonic resections. Although patients can be managed conservatively, some will require re‐intervention with endoscopy, interventional radiology or surgery with significantly increased morbidity and mortality .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, complications such as anastomotic leak and anastomotic bleeding still occur. Fortunately as well as the surgical technique also the possibilities and the modality 'to successfully treat even the most serious post-operative complications are definitely improved (2,3).…”
Section: Introductionmentioning
confidence: 99%